Effects of auricular acupuncture on chronic pain in people with back musculoskeletal disorders: a randomized clinical trial - Caroline de Castro Moura; Erika de Cássia Lopes Chaves; Tânia Couto Machado Chianca; Silvia Graciela Ruginsk; Denismar Alves Nogueira; Denise Hollanda Iunes (SciELO, 2019)
ABSTRACT Objective: To evaluate the effects of auricular acupuncture on pain intensity, its impact on daily activities, the relief provided by the intervention, and the pain threshold in people with back musculoskeletal disorders. Methods: Randomized clinical trial carried out with people randomly allocated into three groups: treatment, placebo, and control. Evaluations were performed using the Brief Pain Inventory and a digital algometer before (initial) and after (final) the treatment and after a 15-day follow-up period. Results: The sample was 110 people. There was a decrease in pain intensity in the treatment and placebo groups as revealed by the comparison between the initial and final evaluations (p<0.05), and in the treatment group in the comparison between the initial and follow-up evaluations (p<0.05). A decreased impact of pain on daily activities in the treatment and placebo groups over time was found (p<0.05). At the final evaluation, the impact of pain was lower in the treatment group (p<0.05). Auricular acupuncture did not increase the pain threshold. Conclusion: Auricular acupuncture presented positive effects by reducing the chronic pain intensity and its impact on daily activities in people with back musculoskeletal disorders. Brazilian Clinical Trials Registry: RBR-5X69X2